0
$\begingroup$

I am trying to prove the following theorem: Every proposition formula is logically equivalent to a formula in CNF.

As a hint, they say that this can by proven by an induction on the structure of the formula, this is what I have done so far:

Basis: A formula with just one symbol (propositional variable) is already in CNF.

Inductive step: A formula with more than 1 symbol has to be in one of these cases:

1) $$\varphi_1 \land \varphi_2$$ 2) $$\varphi_1 \lor \varphi_2$$ 3) $$\varphi_1 \rightarrow\varphi_2$$ 4) $$¬ \varphi_2$$

Let's consider case 1: $\varphi = \varphi_1 \land \varphi_2$, as $\varphi_1$ and $\varphi_2$ have a CNF equivalent formula(by hypothesis, and let's call them $\varphi_1'$ and $\varphi_2'$), then:

$$\varphi = \varphi_1' \land \varphi_2'$$

Which is CNF, and this proves case 1.

Let's consider a formula with the following structure $\varphi = \varphi_1 \lor \varphi_2$. By hypothesis: $\varphi_1$ y $\varphi_2$ have CNF equivalents ($\varphi_1'$ and $\varphi_2'$), then:

$$\varphi = \varphi_1' \lor \varphi_2'$$

where:

$$ \varphi_1' = \psi_1 \land \psi_2 \land ... \land \psi_m$$ $$ \varphi_2' = \delta_1 \land \delta_2 \land ... \land \delta_n$$

And $\psi$ and $\delta$ are clauses of the form: $$\psi_i = L_1 \lor L_2 \lor ... \lor L_{k_i}$$

Applying distributive property on $\varphi_1'$:

$$\varphi_1' \lor (\delta_1 \land \delta_2 \land ... \land \delta_n)$$ $$= (\varphi_1' \lor \delta_1) \land (\varphi_1' \lor \delta_2) \land ... \land (\varphi_1' \lor \delta_n)$$

Doing the following on each $\delta_i$: $$\delta_i \lor \varphi_1' = \delta_i \lor ( \psi_1 \land \psi_2 \land ... \land \psi_m) = (\delta_i \lor \psi_1) \land ... \land (\delta_i \lor \psi_m)$$

Thus, we get

$$ (\delta_1 \lor \psi_1) \land ... \land (\delta_1 \lor \psi_m) \land$$ $$ (\delta_2 \lor \psi_1) \land ... \land (\delta_2 \lor \psi_m) \land$$ $$.$$ $$.$$ $$.$$ $$ (\delta_n \lor \psi_1) \land ... \land (\delta_n \lor \psi_m)$$

This expression is in CNF, which proves case 2.

For case 3, we have $\varphi = ¬\varphi_1$. By hypothesis $\varphi_1$ has a CNF equivalent(which we'll define $\varphi_1'$).

$$ \varphi_1' = \psi_1 \land \psi_2 \land ... \land \psi_m$$

$$\psi_i = L_{i1} \lor L_{i2} \lor ... \lor L_{ik_i}$$

Then:

$$¬\varphi_1=¬(\psi_1 \land \psi_2 \land ... \land \psi_m)$$

$$= ¬\psi_1 \lor ... \lor ¬\psi_m$$

$$ = (¬L_{11} \land ... \land ¬L_{1k_1}) \lor$$ $$ \ \ (¬L_{21} \land ... \land ¬L_{2k_2}) \lor$$ $$.$$ $$.$$ $$.$$ $$ \ \lor (¬L_{m1} \land ... \land ¬L_{mk_m})$$

And here is where I am stuck. I was thinking on rewritting the last term, to get: $\varphi_1''\lor \varphi_2'' \lor ... \lor \varphi_m''$, and using case 2 to end this proof, however I don't know if I can do this. How should I proceed? (and what about the formalisms?)

best regards

$\endgroup$
1
  • $\begingroup$ I don't understand why they suggested you use induction. You only need to prove that the last column of every truth table can get expressed in conjunctive normal form. $\endgroup$ Commented Oct 1, 2015 at 15:36

1 Answer 1

2
$\begingroup$

Hint

By (repeated) Distributivity, we have :

$[(\psi_1 \land \psi_2) \lor (\sigma_1 \land \sigma_2)] \equiv [(\psi_1 \lor \sigma_1) \land (\psi_1 \lor \sigma_2) \land (\psi_2 \lor \sigma_1) \land (\psi_2 \lor \sigma_2)]$.

Thus, you have to simply "rearrange" the new disjunction of conjuncts (coming from the negation of the original conjunction of disjuncts by De Morgan) in order to produce the needed CNF.

$\endgroup$
1
  • $\begingroup$ got it! thanks, I don't know why I did not think that :O $\endgroup$
    – dpalma
    Commented Oct 1, 2015 at 16:18

You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .